Bioremediation of PAHS from Industrial Refinery Effluents to Highly Valuable Transformed Compounds - Muna, Ibrahim; Makky, Essam A.; Seema, Zareen; Abdelhadi, Tarek F.; Nina Suhaity, Azmi; Jamil, Ismail (Universiti Malaysia Pahang, 2017)

(untitled)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants in the environment, and most highly molecular weight PAHs cause mutagenic, teratogenic and potentially carcinogenic effects. The study aims to screen the bioremediation effects on PAHs to produce new compounds with industrial importance by-products contaminated water using liquid- liquid extraction (LLE) coupled with gas chromatography-mass spectroscopy (GC-MS). Two bacterial isolates out of 13 were selected from PAHs samples contaminated water collected from Kuantan River. PAHs were extracted using dichloromethane from refinery wastewater samples collected from BASF (Petronas chemicals Co.). GC-MS analysis revealed that, the PAHs of petroleum refinery were successfully biodegraded using the most potent bacterial isolates within 15 days incubation periods into new compounds (Guanidine derivative, etc.) with industrial applications compared to control. This research improves our understanding of processes contributing to PAHs degradation in petroleum refinery wastewater to new applications.